Bullous pemphigoid in a 5-month-old baby girl. - Belgaumkar, V.A.; Baag, S.A.; Pradhan, S.N.; Dange, K.; Raj , R. (European Journal of Pediatric Dermatology, 2024)
Vesico-bullous lesions can be caused by different causes, sometimes posing problems of differential diagnosis. A case of bullous pemphigoid was reported in a 5-month-old baby girl, who responded well to corticosteroid treatment and even more so to dapsone.